Abnormalities in Semen Analysis in Male Partners of Infertile Couples at a Tertiary Care Hospital in Garhwal Region of Uttarakhand (GAIMS Journal of Medical Sciences, 2024)
Background: Infertility is “failure to achieve a clinical pregnancy after >= 12 months of regular unprotected sexual intercourse”. Abnormal semen parameters are found in 50% of the infertile couples. Thus, Semen analysis is usually the first step in  evaluating male partner in infertile couples.Material and methods: This is a 2 years retrospective study including 103 cases. Patient’s clinical history was taken and Semen sample was obtained by masturbation in sterile universal container following abstinence of 3-5 days. Using WHO standards, Samples were examined for various physical parameters and sperm motility. Sperms were counted with improved neubauer chamber and stained with Pap stain to observe morphology.Results: Total 103 male partners of infertile couples were investigated. Abnormal seminal parameters were found in 57.2% with maximum number in 4th decade (41.7%). Abnormal appearances included transparent (5.8%), opaque (1.9%) and redish brown (1.9%). Hypospermia was seen in 23.3% and increased liquefaction time in 1.9% samples. Sperm concentration and total sperms/ejaculate were reduced in 30.7 % and 31.7% cases respectively. Total Sperm motility was below WHO lower reference range in 16.5% cases. However, progressive motility alone was below lower reference range in 25.8% cases. On morphology, maximum defects were seen in the head of spermatozoa. Leucocytospermia was seen in in 9.9 % . Abnormalities in sperm count  included oligozoospermia (21.4%), Cryptozoospermia (2.9%) and azoospermia (3.9%). Oligozoospermia was the commonest microscopic abnormality followed by Asthenozoospermia (14.6%).Conclusion: Semen analysis is the cornerstone of investigating male infertility.